A NOTE ON THE CAFIERO CRITERION IN EFFECT ALGEBRAS - Barbieri, Giuseppina (Italian Journal of Pure and Applied Mathematics, 2015)
We give an alternative proof of a Cafiero type theorem for measures on eﬀect algebras.